Determinação do coeficiente cromatográfico de partição, log kw, de inibidores da bomba H+/K+ - ATPase - Coimbra, Mariana (Universidade Federal de São Carlos, 2007)
The relative retention and enantioselectivity of a homologue series constituted by five benzimidazoles, K+/H+ - ATPase pump inhibitors, was determined for three amylose tris-phenylcarbamate chiral stationary phases (CSP), under reverse and normal phase modes of elution, using ethanol as a organic modifier. It was verified similar retention profiles for the benzimidazoles homologue series on the three evaluated chiral phases, under reversed mode of elution. The switch between reversed to polar organic mode of elution, under same conditions of reversed mode, and even with a percentage of water, in the mobile phase, around 15% it is clearly observed and discussed. Also, the benzimidazoles series retention profiles on three chiral columns were similar when in the normal elution mode. However, a switch from normal to polar organic mode is slow, indicating that retention/separation mechanisms, that operate in both elution modes, are very comparable. The discrimination chiral capacity of these stationary phases was differentiated when ethanol was used as organic modifier on three elution modes. The amylose tris (3,5 dimethylphenylcarbamate) phase (CSP-2) showed high resolution (Rs) power (0.90 ¡Ü Rs ¡Ü 3.46 and 1.25 ¡Ü á ¡Ü 2.24) for omeprazole enantiomers on the three elution modes. The amylose tris [(S)-phenyethyllcarbamate) phase (CSP-3), in turn, display resolution capacity for all series of homologous enantiomers in normal mode of elution. Herein, it was established for first time a relation between normal and reversed elution mode through the isoelution point determination. Under the same percentage of ethanol, in normal mode, and water in reversed mode, the retentions are similar, when polysaccharides phases are used as chiral selectors. The enantiomeric separations of enantiomers series were carried out in multimilligram scale, and the determination of its elution order was evaluated in the three elution modes. The omeprazole enantiomers separation was performed in multimilligram scale, as a model, using the solid-phase injection technique. The results were compared with those obtained from the separation by means of classical volume injection of sample. These results are presented and discussed.
Determination of chromatographic partition coefficient, Log kw, of h+/k+- atpase pump inhibitors
Keywords: Cromatografia líquida de alta eficiência; Sulfóxidos quirais; Colunas de polissacarídeos; Multimodal; Seletor quiral; CIENCIAS EXATAS E DA TERRA::QUIMICA